Tough photopolymers based on vinyl esters for biomedical applications. Issue 13 (9th February 2016) - Mautner, Andreas; Steinbauer, Barbara; Orman, Sandra; Russmüller, Günter; Macfelda, Karin; Koch, Thomas; Stampfl, Jürgen; Liska, Robert
ABSTRACT: Photocurable vinyl esters have recently been introduced as suitable alternatives to (meth)acrylates in biomedical applications. While (meth)acrylates exhibit good mechanical properties, their cytotoxicity and degradation products principally disqualify them from medical use. Vinyl esters exhibit much lower cytotoxicity and give biocompatible degradation products, but their disadvantage are relatively low mechanical properties, particularly brittleness. This study focuses on the identification of suitable functional groups that are capable of introducing enhanced impact strength into the vinyl ester network, for example, cyclic structures or urethane groups. A new pathway for the synthesis of vinyl esters carrying these groups was established and resulting monomers were tested regarding their photoreactivity and cytotoxicity. Mechanical properties and degradation behavior of the new materials were investigated as well. In addition, the thiol‐ene reaction was utilized to enhance photoreactivity and tune hydrolytical degradation. The new vinyl esters exhibit excellent biocompatibility and good photoreactivity that can be significantly enhanced with thiols on to the level of highly photoreactive acrylates. Ultimately, the impact strength was improved by a factor of more than ten compared to commercial vinyl esters. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1987–1997 Abstract : Vinyl esters are versatile alternatives to (meth)acrylates in biomedical applications due to low toxicity and unproblematic degradation products. Unfortunately, their limited mechanical properties, especially their brittleness, are a shortcoming so far. To improve mechanical properties via the introduction of certain functional groups, we have developed a new synthesis route to vinyl esters and synthesized new types of these monomer class, which upon polymerization give polymers with significantly improved impact strength.